THE SURRENDER OF A PANOPLY OF COPYCATS TO THE CASE-HARDENED MARKET LEADER: SUBSTANTIATION FROM AN EXPERIMENTAL STUDY OF THE INDONESIA CROP-PROTECTION INDUSTRY - Iwan Gunawan; Achmad Sudiro; Ainur Rofiq (University of Merdeka Malang, 2019)
This study has three objectives: to reveal how to create effective copycats design; to determine the most favorable situation for copycats; to cognize the winner of panoplied copycats versus market leader. Study 1 with participation of 98 farmers revealed that copycats managed to steal quality image of market leader through imitation of typography and colour. Study 2 with involvement of 216 farmers suggested that copycat to situate farmer peers as referrals, apply moderately-lower pricing and persuade consumers without sales promotions. Market leader won against copycats in the battle for defending loyal consumers. DOI : https://doi.org/10.26905/jbm.v6i1.3033